Penataan Pengawasan DPR Terhadap Presiden dalam Rangka Penguatan Sistem Presidensial Indonesia - Sihotang, Januari; Berlian; Permai Yudi (Fundamental: Jurnal Ilmiah Hukum, 2024)
The use of DPR oversight instruments such as the right to interrelate, questionnaires and express opinions is not always directly proportional to improving governance. The problem is, first, the monitoring instruments are often used as a means of exchanging political interests. In fact, this nation's energy has been very much depleted, both in terms of time and funds in the proposed monitoring instrument. Second, the implications of the implementation of the DPR's oversight function are no longer within the frame of checks and balances, but have turned into a kind of accountability forum and interfered with the President's prerogative. As a result, the practice of supervision within the frame of Indonesia's presidential system has led to the parliamentary system pendulum. This is indicated by the provision of Article 74 of Law Number 2 of 2018 which regulates that each party (including the President) must implement the DPR's recommendation. If the recommendation is not implemented by the President, then the Parliament can follow it up with the right of interpellation, questionnaire or expressing opinions. If those who do not implement the recommendation are officials within the scope of the Presidential institution, the President must impose sanctions on those concerned. This arrangement is considered to have interfered with the President's prerogative rights and is in conflict with the characteristics of Indonesia's presidential system. Therefore, it is time for DPR oversight to focus on the use of the legislative function and the budget function.